Sous la plage, les pavés! Stranden mellem utopi og dystopi i nyere amerikansk litteratur - Andersen, Tore Rye (K&K - Kultur og Klasse, 2020)
Throughout literary history the beach has often functioned as a utopian counterimage to the purposeful rationality which has shaped our society since the Enlightenment. However, during the 20th Century cracks and fissures have appeared in literature’s utopian ideas of and depictions of the beach. This tendency is closely aligned with the general waning of the utopian ideas that critics like Russel Jacoby find in late capitalism. At the same time, other critics, including Fredric Jameson and Miguel Abensour, insist on the continued relevance of utopia. Through a critical dialogue with some of these critics, the article analyzes two American 21st Century novels whose depictions of the beach combine utopian and dystopian impulses in complex ways: Cormac McCarthy’s The Road (2006) and Thomas Pynchon’s Inherent Vice (2009). Both novels contain the same unusual movement: In the beginning of the stories, both authors depict the beach in a positive fashion that draws on traditional notions of the beach as a utopian refuge. During the stories, however, the utopian ideas are gradually dismantled, and rather than serving as a desirable endgoal, in both novels the fragile refuge of the beach ends up functioning as a dystopian reminder of what has been lost. The article analyzes the complex tensions that characterize this figure of the beach as promised utopia but actual dystopia.